1974
DOI: 10.2170/jjphysiol.24.101
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Mechanical Response of the Smooth Muscles of Pregnant Mouse Myometrium and Guinea Pig Ileum by Cadmium and Manganese Ions

Abstract: Summary Effects of divalent cations on pregnant mouse myometrium and guinea pig ileum were investigated by recording electrical and mechanical activities. 1. Application of transition metal cations (Mn, Cd, Co, Ni, and Zn) inhibited the spontaneous activities of mouse myometrium. Except for Mn, treatment with these cations in a concentration of 1 mM and for 1-2 min caused an irreversible suppression of the mechanical response. 2. Myometrial membrane was hyperpolarized with 0.5 mM Cd decreasing membrane resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…MnCl2 also possessed multiple actions on the mechanical response of smooth muscle cells of the antrum, namely, this agent suppressed the spontaneous contraction, suppressed the Ca-induced contraction evoked by application of Ca in the Ca-free solution in polarized and depolarized muscles, and prevented the leakage ofCa from the store site, under conditions ofCa-free solution. It was also reported that MnCl2 modifies the Ca influx and penetrates the cell, thus causing either a suppression (Keene, Seidel & Bohr, 1972;Katase & Tomita, 1972;Osa, 1974;Yoshida et al 1977) or an acceleration of the mechanical responses (Shibata, 1969;Ogasawara et al 1980) Fig. 8A, the amplitude of the 10mM-Mn (8 mm free Mn)-induced contraction was much smaller than the contraction evoked by 1 x 10-6 M-Ca and such may in part be due to a reduction in the Mg-ATP concentration with production of the Mn-ATP complex.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…MnCl2 also possessed multiple actions on the mechanical response of smooth muscle cells of the antrum, namely, this agent suppressed the spontaneous contraction, suppressed the Ca-induced contraction evoked by application of Ca in the Ca-free solution in polarized and depolarized muscles, and prevented the leakage ofCa from the store site, under conditions ofCa-free solution. It was also reported that MnCl2 modifies the Ca influx and penetrates the cell, thus causing either a suppression (Keene, Seidel & Bohr, 1972;Katase & Tomita, 1972;Osa, 1974;Yoshida et al 1977) or an acceleration of the mechanical responses (Shibata, 1969;Ogasawara et al 1980) Fig. 8A, the amplitude of the 10mM-Mn (8 mm free Mn)-induced contraction was much smaller than the contraction evoked by 1 x 10-6 M-Ca and such may in part be due to a reduction in the Mg-ATP concentration with production of the Mn-ATP complex.…”
Section: Discussionmentioning
confidence: 81%
“…MnCl2 suppressed the Ca spike in visceral smooth muscles (Brading et al 1969;Osa, 1974;. MnCl2 also possessed multiple actions on the mechanical response of smooth muscle cells of the antrum, namely, this agent suppressed the spontaneous contraction, suppressed the Ca-induced contraction evoked by application of Ca in the Ca-free solution in polarized and depolarized muscles, and prevented the leakage ofCa from the store site, under conditions ofCa-free solution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, the enhancement of f-adrenoceptor inhibition by Mg application via an intracellular process has been proposed in some smooth muscle tissues (myometrium, Maruta & Osa, 1989; taenia, Bolton, 1979;Weiss, 1981). Yet its action on contraction is complicated, and is not fully understood; MnCl2 modifies the Ca influx and penetrates the cell, thus causing either a suppression (Keene et al, 1972) or an acceleration (Shibata, 1969;Osa, 1974;Sakai & Uchida, 1981;Itoh et al, 1982;Lategan & Brading, 1988) of the mechanical responses in various visceral muscles. Intracellular accumulation of Mn was experimentally proved to occur in rat ventricular muscle, in which the baseline tension was gradually elevated when exposed to 0.2mm Mn (Chapman & Ellis, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…MnCI2 inhibits the spike generation and produces either a suppression (Keene et al, 1972;Katase & Tomita, 1972;Osa, 1974;Yoshida et al, 1977) or an acceleration of the mechanical responses (Shibata, 1969;Ogasawara et al, 1980). In the guinea-pig portal vein, MnCl2 inhibited the Ca-spike and Ca influxes in polarized and depolarized membranes, thus suppressing the contraction, while MnCl2 may suppress the leakage of Ca from storage sites after re-addition of Ca to the Ca-free solution and enhance the contraction evoked by either caffeine or NA.…”
Section: Methodsmentioning
confidence: 99%